The Blockage of the WTO Appellate Body: Some Notes on State Responsibility and Dispute Settlement in International Trade - Infante Caffi, Horacio; Tagle Ramírez, Felipe (Revista Tribuna Internacional, 2021)
The United States has not agreed to appoint members to the six vacant positions in the WTO Appellate Body. This is known as the blockage of the AB, based on various criticisms but apparently on a trade strategy to strengthen its position on China, within the context of a trade war with that country. The blockage of the AB affects the dispute settlement system and seriously compromises WTO trade system itself. The main purposes of thie article are: i.- to analyze whether there is international responsibility in the blockage of the AB, and ii.- to consider possible solutions to this blockage within and outside of the WTO legal system.